2008
DOI: 10.1007/s11746-008-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hydroxyl Content of Soybean Polyols

Abstract: Polyurethanes are obtained by reacting polyols with polyisocyanates. The primary hydroxyl content is a very important characteristic of polyols because it affects their reactivity. Typically primary hydroxyls are approximately threefold more reactive than the secondary hydroxyls when reacting with aromatic isocyanates. This paper presents a simple and convenient kinetic method for determining the primary hydroxyl content in soybean polyols, based on the difference in reactivity of primary and secondary hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…From Table 3, it is found that the OH numbers reasonably increase linearly with the increase of COD content while viscosity decreases. It is well known that primary hydroxyl groups are approximately 3.3-fold more reactive than secondary hydroxyl groups [26], Thus more content of COD provided more reactive primary hydroxyl groups to react with ESBO, and then more epoxy groups were ring-opened by the primary hydroxyl groups in COD, instead of being ring-opened by the newly generated secondary hydroxyl groups. Therefore, the cross-link densities decrease resulting in relatively lower viscosity as shown in Figure 13.…”
Section: Effect Of Reactionmentioning
confidence: 99%
“…From Table 3, it is found that the OH numbers reasonably increase linearly with the increase of COD content while viscosity decreases. It is well known that primary hydroxyl groups are approximately 3.3-fold more reactive than secondary hydroxyl groups [26], Thus more content of COD provided more reactive primary hydroxyl groups to react with ESBO, and then more epoxy groups were ring-opened by the primary hydroxyl groups in COD, instead of being ring-opened by the newly generated secondary hydroxyl groups. Therefore, the cross-link densities decrease resulting in relatively lower viscosity as shown in Figure 13.…”
Section: Effect Of Reactionmentioning
confidence: 99%
“…Ring‐opening by different short‐chain alcohols often used as solvents have also been performed, methanol being preferred for best results at low‐cost. Different epoxidized vegetal oils were treated in boiling methanol or with allylic alcohol in the presence of tetrafluoroboric acid leading to mixtures containing transesterification or oligomerization by‐products . p ‐Toluene sulfonic acid or BF 3 allowed the selective ring‐opening with 2‐ethylhexanol at 120°C, whereas sulfuric acid or Dowex 50W‐X8 led to competitive transesterification .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of pure alcohols, even tertiary alcohols reacted fully with TSI within 2 min. The relative error values obtained for 1°and 2°alcohols, ranged from 0.13 to 1.17 vs. 0.54 to 1.85 %, respectively, indicating that there were no substantive differences between 1°and 2°alcohols reacting with TSI, whereas 2°alcohols are known to be about *39 less reactive with phenylisocyanate [14]. Carboxylic acids, as represented by nonanoic acid, were determined to be non-reactive while benzylamine did react with TSI resulting in a decrease in the intensity of the isocyanate absorption; however, the spectral changes produced did not affect the carbamate region where measurements are being made.…”
Section: Variables Affecting Quantitationmentioning
confidence: 88%
“…The linear regression equations and statistics obtained for the TSI-FTIR and AOCS results relative to the calculated theoretical (OHV T ) values are presented in Eqs. (14) and (15):…”
Section: General Conceptsmentioning
confidence: 99%